Exploring A Right Not To Be Offended In One’s Religious Beliefs - Sindhu, R (The Department of Law, Faculty of Arts, University of Jaffna / Surana and surana International Attorneys India, 2025)
This essay examines if freedom of religion in Sri Lanka includes a right not to be offended in one’s religious beliefs. The Constitution of Sri Lanka guarantees an absolute right to freedom of religion, while the right to manifest one’s religion is subject to restrictions. While Sri Lankan jurisprudence in relation to religious insult or criticism is limited, an expectation of a right not to be offended can be inferred from judicial attitudes, behaviour of law enforcement societies and societal responses. Incidents such as the publication of Budunge Rasthiyaduwa, arrest of a woman for wearing a Dharma Chakraya on clothing and Natasha Edirisooriya’s stand-up comedy are pertinent. Furthermore, the European Court of Human Rights (EctHR) has recognised such a right, justifying the restriction of religious insults as necessary in a democratic society, for legitimate aims such as preventing disorder or protecting the rights of others. For example, in Otto-Preminger-Institut v Austria the court upheld the banning of a film which involved provocative portrayals of God. The ECtHR weighed the conflicting interests of freedom of expression and respect to religious beliefs and held that respect to the religious feelings of believers was violated by provocative depictions of objects of religious veneration. I argue that there should be no right to not be offended in one’s religious beliefs. While the freedom to share expressions about religion is not absolute, offence should not be a reason to restrict the freedom of expression.
Keywords: Religious offence; Freedom of religion; Insults; Freedom of expression; Criticism